2022
DOI: 10.1007/s10072-022-06010-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of kinesiology taping on the functions of upper limbs in patients with stroke: a meta-analysis of randomized trial

Abstract: Background Kinesiology tape (KT), a water-resistant and elastic tape which is well known measure for preventing musculoskeletal injuries, has recently gained popularity in neurological rehabilitation. This is a systematic and meta-analysis study, useful both to evaluate the efficacy of kinesiology taping on the functions of upper limbs in patients with stroke and to collect the main outcomes evaluated in the analyzed studies. Methods A comprehensive litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
2
9
0
5
Order By: Relevance
“…Kinesiology taping can be an alternative intervention for patients with hemiplegic shoulder pain. According to a meta-analysis by Wang et al [ 50 ], kinesiology taping can be recommended to improve pain, SSD, disability, upper extremity function, and ROM. Thus, previous studies support the shoulder kinesiology taping method that was used to perform the role of the deltoid and external rotator in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Kinesiology taping can be an alternative intervention for patients with hemiplegic shoulder pain. According to a meta-analysis by Wang et al [ 50 ], kinesiology taping can be recommended to improve pain, SSD, disability, upper extremity function, and ROM. Thus, previous studies support the shoulder kinesiology taping method that was used to perform the role of the deltoid and external rotator in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies on the combined effects of spasticity treatments have been conducted on the lower limbs [10]. A meta-analysis on the application of taping to the upper extremities demonstrated that it was effective for shoulder pain, subluxation, disability, upper extremity function, and range of motion [26]; however, the evidence for its effects on spasticity was reported to be weak due to a lack of related studies. We hypothesized that the simultaneous application of TENS and taping in stroke patients would be effective in improving spasticity, strength, and motor function compared to TENS alone.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre os objetivos descritos na literatura, a BEF auxilia na contração e na função motora da musculatura enfraquecida, nas circulações sanguínea e linfática e no favorecimento do aumento da propriocepção por excitação dos mecanorreceptores cutâneos (11,12) . A BEF pode promover estímulos sensoriais e mecânicos duradouros e constantes na pele, acionar o sistema nervoso central, ocorrendo recrutamento de neurônios motores o que resulta em aumento do tônus muscular e pode auxiliar na neuroplasticidade (11,13,14) .…”
Section: Introductionunclassified